Identification of the Addition Effect from Duwet Fruit Extract (Syzygium cumini) on Cigarette Filter Against the Magnetic Character of Cigarette Smoke - Rohul Hayati; Djoko Harry Santjojo; Johan A. E Noor (Natural B, Journal of Health and Environmental Sciences, 2016)
Cigarette smoke is heterogeneous aerosol which resulted from imperfect burn of tobacco leaf that contain gas and particle component which very potential as free radical. The amount of radical content in this cigarette smoke can be reduced by bioactive compounds which functions as radical scavenger such as what is contained in the java plum (Syzygium cumini) plant and can be identified through its magnetic character. The aim of this research was to assess and analyze magnetic character from cigarette smoke before (empty cigarette smoke) and after the addition of java plum squeeze extract to the filter (cigarette smoke of java plum) by using instrument set of ESR. This research showed that with the addition of java plum squeeze extract, it could alter magnetic character of cigarette smoke becomes more paramagnetic which seen from the difference of energy level (∆E) under the influence ofan external magnetic field, Besides the changes in the form of splitting of energy in cigarette smoke Duwet marked by changes in the value of energy groundstate more significant to the external magnetic field that is interpreted that the smoke Duwet have ferromagnetic properties more than an empty cigarette smoke.